Recent Progress on Hybrid Nanofluids In Heat Transfer Applications: A Comprehensive Review - Nor Azwadi, Che Sidik; Isa Muhammad, Adamu; Muhammad Mahmud, Jamil; Kefayati, G. H. R.; R., Mamat; G., Najafi (Elsevier, 2016)
Hybrid nanofluids are potential fluids that offer better heat transfer performance and thermo physical properties than convectional heat transfer fluids (oil, water and ethylene glycol) and nanofluids with single nanoparticles. Hybrid nanofluid is a new nanotechnology fluid that is synthesized by dispersing two different nanoparticles into conventional heat transfer fluid. Recently, researchers have indicated that hybrid nanofluids can effectively substitute the convectional coolant especially those working at very high temperatures. In this paper a comprehensive literature on synthesis of hybrid nanoparticles, hybrid nanofluid and thermophysical properties of hybrid nanofluids have been compiled and reviewed. Finally, the challenges and future trends in the application of hybrid nanofluids in heat transfer applications are discussed.